Security Suite (International Journal of Engineering and Computer Science, 2017)
Now a days information security is become a basic need in this digital world. It is very important to protect the information from various intruders. The system on which information is stored should not be vulnerable to E-mail attacks such as phishing, E-mail date and time spoofing E-mail address spoofing, as well as various malware attacks. This project presents basic protection that can be provided to the system .It illustrates E-mail forensics to detect E-mail Date and Time spoofing as well as E-mail address spoofing. We have created dataset of spoofed and legitimate E-mails. We propose a technique to perform the analysis of E-mail, by reading the header information and analyzing the fields related to date and time as well as sender and receiver address. We have also given an introduction to various malware detection techniques. We have described hash based malware detection technique. Here we have compare the hash values of input file with the database of bad hash values to detect virus.